2014
DOI: 10.1371/journal.pone.0090567
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus Infections Enhance Cigarette Smoke Induced COPD in Mice

Abstract: Respiratory syncytial viral (RSV) infections are a frequent cause of chronic obstructive pulmonary disease (COPD) exacerbations, which are a major factor in disease progression and mortality. RSV is able to evade antiviral defenses to persist in the lungs of COPD patients. Though RSV infection has been identified in COPD, its contribution to cigarette smoke-induced airway inflammation and lung tissue destruction has not been established. Here we examine the long-term effects of cigarette smoke exposure, in com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
62
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 72 publications
7
62
0
1
Order By: Relevance
“…In addition, daily intake of Lactobacillus casei Shirota increased the cytotoxic activity of natural killer cells as well as CD16 + cells in current smokers 153 . Respiratory syncytial virus infection can lead to significant airspace enlargement and fibrosis in mice exposed to cigarette smoke, as well as heightened disease severity in mice 154 . Notably, administration of L. rhamnosus before respiratory syncytial virus infection in mice resulted in elevated antiviral responses via TLR3/RIG‐I activation 155 .…”
Section: The Role Of the Microbiome In Copdmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, daily intake of Lactobacillus casei Shirota increased the cytotoxic activity of natural killer cells as well as CD16 + cells in current smokers 153 . Respiratory syncytial virus infection can lead to significant airspace enlargement and fibrosis in mice exposed to cigarette smoke, as well as heightened disease severity in mice 154 . Notably, administration of L. rhamnosus before respiratory syncytial virus infection in mice resulted in elevated antiviral responses via TLR3/RIG‐I activation 155 .…”
Section: The Role Of the Microbiome In Copdmentioning
confidence: 99%
“…153 Respiratory syncytial virus infection can lead to significant airspace enlargement and fibrosis in mice exposed to cigarette smoke, as well as heightened disease severity in mice. 154 Notably, administration of L. rhamnosus before respiratory syncytial virus infection in mice resulted in elevated antiviral responses via TLR3/RIG-I activation. 155 Although the role of microbiome in COPD needs to be further investigated, early studies have suggested an association between both lung and gut microbiota and the outcomes of disease.…”
Section: The Role Of the Microbiome In Copdmentioning
confidence: 99%
“…Several studies have reported that exacerbation with bacteria ( H. influenzae ), virus (rhinovirus), or a surrogate for virus-induced innate immunity (poly(I:C)) accelerates the progression of cigarette smoke-induced emphysema in mice (Foronjy, et al, 2014, Ganesan, et al, 2014, Kang, et al, 2008, Tanabe, et al, 2013). In addition, mice exposed to cigarette smoke and then infected with influenza virus H1N1 or H3N1 had increased in the number of immune cells in the BAL fluid and a 10-fold increase in lung virus titers (Bauer, et al, 2010, Gualano, et al, 2008).…”
Section: Innate and Adaptive Immunity In The Pathogenesis Of Emphymentioning
confidence: 99%
“…Кроме того, RSV и табачный дым синергично ак-тивировали апоптоз респираторного эпителия и подавляли экс-прессию фосфатаз, оказывающих противовоспалительное и ан-типротеазное действие. В результате сочетание этих двух пато-генных факторов приводило к выраженному фиброзу и ремоде-лированию дыхательных путей [49].…”
Section: терапевтический архив 3 2015unclassified